2015
DOI: 10.3390/healthcare3040933
|View full text |Cite
|
Sign up to set email alerts
|

From Their Voices: Barriers to HIV Testing among Black Men Who Have Sex with Men Remain

Abstract: BackgroundHIV testing continues to be a major priority for addressing the epidemic among young Black men who have sex with men (BMSM).MethodsThis study explored barriers to HIV testing uptake, and recommendations for motivating HIV testing uptake among Black men who have sex with men (BMSM) aged 18 to 30. BMSM (N = 36) were recruited through flyers and social media for six focus groups.ResultsFrom the perspectives and experiences of young BMSM, participants recommended that information be included in HIV testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…The present study is a pilot study with a small sample size, and, as such, these results should be interpreted with caution; however, they provide preliminary support for findings that could be further evaluated by larger scale studies. In previous research, these barriers have been identified as places of weakness in the HIV continuum of care, particularly for the most vulnerable communities (eg, BMSM), for whom the burden of undetected HIV infection strongly persists [2,35,36]. Arguably, these barriers may have been lessened because of the Web-based nature of this study.…”
Section: Discussionmentioning
confidence: 93%
“…The present study is a pilot study with a small sample size, and, as such, these results should be interpreted with caution; however, they provide preliminary support for findings that could be further evaluated by larger scale studies. In previous research, these barriers have been identified as places of weakness in the HIV continuum of care, particularly for the most vulnerable communities (eg, BMSM), for whom the burden of undetected HIV infection strongly persists [2,35,36]. Arguably, these barriers may have been lessened because of the Web-based nature of this study.…”
Section: Discussionmentioning
confidence: 93%
“…Black and Latino MSM are among the most challenging groups for the scale-up of PrEP. Barriers could include limited access to quality healthcare, poverty, lack of or poorer health insurance coverage, and higher rates of incarceration [51,52,53]. A study by Oster et al, however, found that similar rates of newly diagnosed Black and White MSM had health insurance, saw a provider, and received HIV screening tests [54].…”
Section: Discussionmentioning
confidence: 99%
“…These beliefs have impeded treatment efforts among HIV-positive individuals because of their desire for secrecy or reluctance to disclose to partners (Earnshaw & Chaudoir, 2009). Among those with unknown status, fear of receiving a positive HIV test result remains a potent disincentive to seeking HIV testing (Valdiserri, Holtgrave, & West, 1999; Obermeyer & Osborn, 2007; Otto-Salaj et al, 2008; Washington et al, 2015). HIV stigma has the potential to impede the uptake of a novel and highly effective HIV biomedical prevention methods, specifically post-exposure prophylaxis (PEP) and pre-exposure prophylaxis (PrEP) (van der Straten et al, 2014; Calabrese & Underhill, 2015).…”
Section: Discussionmentioning
confidence: 99%